KLF9-GRK5-HDAC6 axis aggravates osteoarthritis pathogenesis by promoting chondrocyte extracellular matrix degradation and apoptosis - Xiaonan Zhou; Peng Jiang; Huangqi Tan; Yanfang Wang; Lunhao Bai (Communications Biology)
Abstract Osteoarthritis (OA) is a degenerative joint disease that affects the cartilage and surrounding tissues. The transcription factor Kruppel-like family factor 9 (KLF9) has been identified as a regulator of tumorigenesis. However, its role in OA is still not fully understood. Herein, this study aimed to access the potential role and molecular mechanism by which KLF9 regulates OA development. KLF9 was upregulated in cartilage tissues of OA patients and medial meniscotibial ligament (MMTL)-induced OA rats, as well as in IL-1β-treated chondrocytes. Furthermore, knockdown of KLF9 inhibited OA-related cartilage injury, as evidenced by inhibiting chondrocyte extracellular matrix (ECM) degradation, increasing chondrocyte viability, and decreasing apoptosis. Conversely, overexpression of KLF9 had the opposite effect. The downstream mechanism of KLF9 was confirmed. KLF9 mediated the transcription of G protein-coupled receptor kinase 5 (GRK5) by directly targeting the GRK5 promoter. GRK5 knockdown eliminated the effects of KLF9 overexpression on chondrocyte dysfunction. It was also found that GRK5 combined with histone deacetylase 6 (HDAC6) and promoted HDAC6 phosphorylation. The use of the HDAC6 inhibitor TubastatinA also abolished the effects of GRK5 overexpression on chondrocyte ECM degradation and apoptosis. These results demonstrate that the KLF9-GRK5-HDAC6 axis plays a crucial role in promoting the progression of OA.